2020
DOI: 10.1182/blood.2020005045
|View full text |Cite
|
Sign up to set email alerts
|

Progressive vasoconstriction with sequential thermal stimulation indicates vascular dysautonomia in sickle cell disease

Abstract: Sickle cell disease (SCD) subjects exhibit subjective hypersensitivity to cold and heat perception in experimental settings, and triggers such as cold exposure are known to precipitate vaso-occlusive crisis by still unclear mechanisms. Decreased microvascular blood flow (MBF) increases the likelihood of vaso-occlusion by increasing entrapment of sickled red blood cells in the microvasculature. As SCD subjects have dysautonomia, we anticipated that thermal exposure would induce autonomic hypersensitivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Consistent with this finding, Willen et al 16 showed no significant association between low mean nocturnal SpO 2 and incidence of VOC in the SAC participants studied here. On the other hand, we 5,7,8,24,25 and others 26‐29 have shown significant dysautonomia in SCD. Therefore, we examined measures of cardiac ANS balance (LHR, RMSSD) but found no association with VOC rate (modesl 8‐9 Table S2).…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with this finding, Willen et al 16 showed no significant association between low mean nocturnal SpO 2 and incidence of VOC in the SAC participants studied here. On the other hand, we 5,7,8,24,25 and others 26‐29 have shown significant dysautonomia in SCD. Therefore, we examined measures of cardiac ANS balance (LHR, RMSSD) but found no association with VOC rate (modesl 8‐9 Table S2).…”
Section: Discussionmentioning
confidence: 62%
“…While we found that interindividual variability of BRSv contributes to the variability in vasoconstriction responses across individuals, adjusting for differences in BRSv actually further reduced the inter-group differences in MTS-induced vasoconstriction responses (Figure 4B). This stands in contrast with the enhanced vasoconstriction responses found in SCD subjects during thermal pain stimuli (Khaleel et al, 2017;Veluswamy et al, 2020). Since there is increasing evidence that dysautonomia in SCD is associated with autonomic hyperresponsiveness, one would have expected the SCD subjects with high sympathetic tone to have displayed stronger vasoconstriction responses to MTS.…”
Section: Variability Of Vasoconstriction Responses Resulting From Differences In Source Of Autonomic Stimulationmentioning
confidence: 83%
“…In a previous study ( Shah et al, 2020 ), we measured the cardiovascular responses of SCD and healthy subjects to MTS tasks that included N-back, Stroop, and anticipated pain tests. However, in contrast to physical autonomic stressors, such as heat pain and cold pain, where SCD subjects showed exaggerated vasoconstriction responses ( Khaleel et al, 2017 ; Veluswamy et al, 2020 ), the responses of the SCD subjects to MTS were not different from their control counterparts. However, there is substantial variability in the magnitude of the responses within the SCD and control subjects.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Chiesa et al have described excellent outcomes after allogeneic hematopoietic cell transplantation (allo-HCT) for 712 patients with chronic granulomatous disease (CGD). This study reports the largest published cohort to date by a significant margin 1. As a young hematologist set on becoming a transplanter, I sought advice from someone more experienced than myself, and one of my colleagues replied, "Know as much as you can about the underlying disease.…”
mentioning
confidence: 99%